ON THE ISSUE OF ORGANIZATION OF DISTANCE LEARNING IN THE DISCIPLINE "INFECTIOUS DISEASES" - Давыденко, Оксана; Мироник, Елена (SWorldJournal, 2020)
The paper considers the organization of the educational process in the discipline "Infectious Diseases" using distance learning. The advantages of distance learning in high school are described. Distance learning opens up completely new opportunities for